A Note on the Estimation of Job Amenities and Labor Productivity - Arnaud Dupuy; Alfred Galichon (Institute of Labor Economics (IZA), 2017)
This note introduces a maximum likelihood estimator of the value of job amenities and labor productivity in a single matching market based on the observation of equilibrium matches and wages. The estimation procedure simultaneously fits both the matching patterns and the wage curve. Our estimator is suited for applications to a wide range of assignment problems.
Keywords: C35; C78; J31; 330; matching; observed transfers; structural estimation; value of job amenities; value of productivity